2011
DOI: 10.1016/j.anbehav.2011.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of predators and nonpredators by juvenile rainbow trout: learning what is and is not a threat

Abstract: Learned recognition of novel predators allows prey to respond to ecologically relevant 27 threats. Prey could minimize the costs associated with learning the identity of both 28 predators and nonpredators by making educated guesses on the identity of a novel species 29 based on their similarities with known predators and nonpredators, a process known as 30 generalization. Here, we tested whether juvenile rainbow trout, Oncorhynchus mykiss, 31have the ability to generalize information from a known predator (exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 51 publications
4
45
0
Order By: Relevance
“…A series of elegant studies with mammals (Griffin et al 2001;Stankowich & Coss 2007), amphibians (Ferrari et al 2009b) and fishes (Ferrari et al 2007(Ferrari et al , 2010bBrown et al 2011a) have shown that prey conditioned to a reference predator can exhibit learned responses to chemical and visual cues of predators with which the prey have no experience. Moreover, predators that are more distantly related to the reference predator are not recognised.…”
Section: Generalising Of Predator Cuesmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of elegant studies with mammals (Griffin et al 2001;Stankowich & Coss 2007), amphibians (Ferrari et al 2009b) and fishes (Ferrari et al 2007(Ferrari et al , 2010bBrown et al 2011a) have shown that prey conditioned to a reference predator can exhibit learned responses to chemical and visual cues of predators with which the prey have no experience. Moreover, predators that are more distantly related to the reference predator are not recognised.…”
Section: Generalising Of Predator Cuesmentioning
confidence: 99%
“…There was no inhibition of learning of rock bass or yellow perch odours. Modified from Brown et al (2011a).…”
Section: Generalisation Of Non-predator Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent evidence suggests that predator recognition is much more sophisticated. For instance, prey species can display an anti-predator response towards a novel predator upon their first encounter if the predator species is related to a species already recognized as dangerous by the prey [26,43]. In amphibians, occurrences of the so-called 'innate' predator recognition in wild populations sympatric with predators (e.g.…”
Section: (B) Rethinking Predator Recognitionmentioning
confidence: 99%
“…A look at the predator recognition literature suggests that not all information available from predators is equal and that different species focus on certain cues whilst ignoring others. For visual features, prey appear to preferentially focus on those that specifically relate to predatory functions, such as the morphology of eyes and their position on the head (Karplus et al 1982;Beránková et al 2014), size and shape of the mouth (Karplus et al 1982), size/shape/silhouette of the body (Engstrom-Ost and Lehtiniemi 2004;Stankowich and Coss 2007;Brown et al 2011) and posture/orientation (Helfman 1989;Cooper 1998;Schluessel et al 2014). Experimentally modifying these features can significantly impact antipredator responses of prey, whilst modifying non-functional features has little or no effect (Karplus et al 1982;Beránková et al 2014).…”
Section: Introductionmentioning
confidence: 96%